The Application Of Human Resources Management: A Case Study In The Library Of The High School Of Agricultural Science-Agrobusiness Plants In Medan (STIP-AP) - Sari, Kurnia; Achiriah; Jamil, Khoirul (International Journal of Cultural and Social Science, 2022)
This study discusses the Application of Human Resource Management: A Case Study in the Library of the College of Agricultural Sciences-Agrobusiness Plantation in Medan. The purpose of this study was to determine the application and barriers to the application of human resource management in the Library of the College of Agricultural Sciences-Agrobusiness Plantation in Medan. The research method used is field research which is descriptive qualitative in nature. Using data collection techniques through observation, interviews and documentation. The informants in this study were librarians and staff at the Library of the College of Agricultural Sciences-Agrobusiness Plantation in Medan. The results showed that the implementation of human resource management in the STIP-AP Medan Library in general, library members were determined by the Deputy Chairman 2 as the Finance and HR Division at STIP-AP Medan. For the application of HR management in the job description made by the Head of the Library, based on a meeting with the staff of the STIP-AP Library, the results of the meeting were then proposed to Deputy Chair 1